A construção da memória : os monumentos a Bento Gonçalves e José Artigas - Fuão, Juarez José Rodrigues (Universidade do Vale do Rio do Sinos, 2009)
The thesis examines the building process of Bento Gonçalves da Silva General grave monument as well as José Gervasio Artigas General monument. The first, built in 1909 and laid in the municipality of Rio Grande, more precisely at Tamandaré Square, and the second, inaugurated in the year of 1923 in Montevideo, at Plaza Independencia. Whereas the monuments represent the materialization of a series of speeches, appropriations and disputes over the memory of the honored heroes the study aims to examine the representations given to these personages along both the intellectual output and the printing press, prior to these public works inauguration.
Keywords: BentoGonçalves; José Artigas; monumento – memória; Uruguai – história; Rio Grande do Sul – história; Ciências Humanas